Granulocyte-Macrophage Colony-Stimulating Factor Modulates Myeloid-Derived Suppressor Cells and Treg Activity in Decompensated Cirrhotic Patients With Sepsis - Sehgal, Rashi; Maiwall, Rakhi; Rajan, Vijayaraghavan; Islam, Mojahidul; Baweja, Sukriti; Kaur, Navkiran; Kumar, Guresh; Ramakrishna, Gayatri; Sarin, Shiv K.; Trehanpati, Nirupma (Frontiers in Immunology, 2022)
Background: Decompensated cirrhosis patients are more prone to bacterial infections. Myeloid derived suppressor cells (MDSCs) expand in sepsis patients and disrupt immune cell functions. GM-CSF therapy helps in restoring immune cell functions and resolve infections. Its role in MDSCs modulation in cirrhotic with sepsis is not well understood. Methods: 164 decompensated cirrhotic; 62 without (w/o), 72 with sepsis and 30 with sepsis treated with GM-CSF and 15 healthy were studied. High-dimensional flow cytometry was performed to analyse MDSCs, monocytes, neutrophils, CD4 T-cells and Tregs at admission, day3 and 7. Ex-vivo co-cultured MDSCs with T-cells were assessed for proliferation and apoptosis of T-cells, differentiation to T-regs. Plasma factors and mRNA levels were analysed by cytokine-bead assay and qRT-PCR. Results: Frequency of TMDSCs and T-regs were significantly increased (p=0.011, and p=0.02) with decreased CD4 T-cells (p=0.01) in sepsis than without sepsis and HC (p=0.000, p=0.07 and p=0.01) at day0, and day7. In sepsis patients, MDSCs had increased IL-10, Arg1 and iNOS mRNA levels (p=0.016, p=0.043 and p=0.045). Ex-vivo co-cultured MDSCs with T-cells drove T-cell apoptosis (p=0.03, p=0.03) with decreased T-cell proliferation and enhanced FOXP3+ expression (p=0.044 and p=0.0.043) in sepsis compared to w/o sepsis at day0. Moreover, blocking the MDSCs with inhibitors suppressed FOXP3 expression. GM-CSF treatment in sepsis patients significantly decreased MDSCs and FOXP3+Tregs but increased CD4 T-cell functionality and improved survival. Conclusion: MDSCs have immunosuppressive function by expanding FOXP3+ Tregs and inhibiting CD4+ T-cell proliferation in sepsis. GM-CSF treatment suppressed MDSCs, improved T-cell functionality and reduced Tregs in circulation.